Birokrasi Sanak Kadang: Benturan Etika Dan Prinsip Birokrasi - Sri Mulyani (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The following article intends to analyze and present the face of bureaucracy in a developing country like Indonesia in its contact with the culture that lives in society. Bureaucracy as a form as well as an efficient way of working as desired by a number of standard principles, of course for a country with cultural wealth or diversity like Indonesia will reap problems if the bureaucracy is required to operate according to its principles. All ideal bureaucratic principles almost all forbid action based on values that live in a culture. The impersonality of the bureaucracy requires its apparatus to carry out all the rules to be enforced regardless of personal or political relations, especially relations of 'sometimes' relatives. Meanwhile, most of the values that live in society operate in the 'territory' of the extended family, where the most pressing demand is the inclusion of considerations of fairness, decency, goodness and others, all of which are evaluated based on a number of ethical principles. It is this ethical evaluation that makes our bureaucracy often inefficient, tends to be convoluted and wasteful. The end of this paper is a recommendation related to public service ethics.